2021
DOI: 10.1159/000521611
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Growth Restriction Disrupts the Postnatal Critical Period of Synaptic Plasticity in the Mouse Dorsal Hippocampus in a Model of Hypertensive Disease of Pregnancy

Abstract: Introduction: Intrauterine growth restriction (IUGR) from hypertensive disease of pregnancy complicates up to 10% of all pregnancies. Significant hippocampal-dependent cognitive and memory impairments as well as neuropsychiatric disorders have been linked to IUGR. Because disturbance of hippocampal critical period (CPd) of synaptic plasticity leads to impairments similar to those described in IUGR human offspring, we hypothesized that IUGR would perturb the CPd of synaptic plasticity in the mouse hippocampus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 82 publications
2
26
2
Order By: Relevance
“…In our mouse model, we examined these phases of the critical period at P10, P18, and P40. We found that at P10, no difference was seen in the number or volume of either PV + interneurons or GAD 65/67 + puncta between sham and IUGR (St Pierre et al, 2022). At P18, however, despite no difference in PV + interneurons, we found increased GAD 65/67 + puncta and volume in IUGR mice in CA pyramidal cell layer compared to sham, suggesting an advanced GABAergic development in IUGR.…”
Section: Critical Period Of Synaptic Plasticitycontrasting
confidence: 51%
See 3 more Smart Citations
“…In our mouse model, we examined these phases of the critical period at P10, P18, and P40. We found that at P10, no difference was seen in the number or volume of either PV + interneurons or GAD 65/67 + puncta between sham and IUGR (St Pierre et al, 2022). At P18, however, despite no difference in PV + interneurons, we found increased GAD 65/67 + puncta and volume in IUGR mice in CA pyramidal cell layer compared to sham, suggesting an advanced GABAergic development in IUGR.…”
Section: Critical Period Of Synaptic Plasticitycontrasting
confidence: 51%
“…At P18, however, despite no difference in PV + interneurons, we found increased GAD 65/67 + puncta and volume in IUGR mice in CA pyramidal cell layer compared to sham, suggesting an advanced GABAergic development in IUGR. At P40, this difference disappeared in IUGR as the sham group caught up in GAD + bouton development (St Pierre et al, 2022). Concurrently at P18, we saw decreased PSA-NCAM expression in the pyramidal cell membranes in IUGR, which normally acts to limit the formation of perisomatic inhibitory GABAergic synapses, but in this case has permitted the accelerated GABAergic synaptic formation in IUGR mice.…”
Section: Critical Period Of Synaptic Plasticitymentioning
confidence: 66%
See 2 more Smart Citations
“…This could be explained by disturbed prenatal neuronal development. St. Pierre et al were able to demonstrate in a murine IUGR model that IUGR is associated with impaired synaptic plasticity in the hippocampus (133). In addition, Brown et al described that IUGR mice show a reduced number of neural stem cells in the hippocampus as well as a disturbed induction of neuronal differentiation.…”
Section: The Etiological Pathway Highlighting the Link Between Iugr A...mentioning
confidence: 99%